A Deadly Infodemic: Social Media and the Power of COVID-19 Misinformation - Michael A Gisondi; Rachel Barber; Jemery Samuel Faust; Ali Raja; Matthew C Strehlow; Lauren M Westafer; Michael Gottlieb (JMIR Publications, 2022)
COVID-19 is currently the third leading cause of death in the United States, and unvaccinated people continue to die in high numbers. Vaccine hesitancy and vaccine refusal are fueled by COVID-19 misinformation and disinformation on social media platforms. This online COVID-19 infodemic has deadly consequences. In this editorial, the authors examine the roles that social media companies play in the COVID-19 infodemic and their obligations to end it. They describe how fake news about the virus developed on social media and acknowledge the initially muted response by the scientific community to counteract misinformation. The authors then challenge social media companies to better mitigate the COVID-19 infodemic, describing legal and ethical imperatives to do so. They close with recommendations for better partnerships with community influencers and implementation scientists, and they provide the next steps for all readers to consider. This guest editorial accompanies the Journal of Medical Internet Research special theme issue, "Social Media, Ethics, and COVID-19 Misinformation."